2020
DOI: 10.1038/s41427-020-00260-1
|View full text |Cite
|
Sign up to set email alerts
|

Flexible high-performance graphene hybrid photodetectors functionalized with gold nanostars and perovskites

Abstract: Hybrid materials in optoelectronic devices can provide synergistic effects that complementarily enhance the properties of each component. Here, flexible high-performance graphene hybrid photodetectors (PDs) are developed by introducing gold nanostars (GNSs) and perovskites for strong light trapping with hot electron transfer and efficient light harvesting characteristics, respectively. While pristine graphene PDs do not exhibit discernible photodetection properties due to the very low photon absorption and ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Also, the device dark current was consistent with that previously reported for integrated-structure PDs. , Figure d show the photo-response rising time (photocurrent from 10 to 90% as a light switch) and decay time (photocurrent from 90 to 10% as a light switch) of the n = 2 G–Au–P-PDs, for which the rise and decay times were 0.33 and 0.27 s, respectively. The photo-response times of the device were shorter than those reported in previous studies. , However, compared with the n = 2 G–Au–P-PDs, the n = 1 G–Au–P-PDs had a lower dark current and faster photo-response time (Figure S13c,d). For the quasi-2D perovskite, the reduction of quantum well thickness, ion migration, and vacancy defect decrease can effectively confine the charge transport within the quantum plane, leading to a severe charge carrier recombination, resulting in both the dark current and photocurrent decrease. , Therefore, the quasi-2D P-PDs with small quantum well thickness showed great potential for ultra-fast photon detection.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…Also, the device dark current was consistent with that previously reported for integrated-structure PDs. , Figure d show the photo-response rising time (photocurrent from 10 to 90% as a light switch) and decay time (photocurrent from 90 to 10% as a light switch) of the n = 2 G–Au–P-PDs, for which the rise and decay times were 0.33 and 0.27 s, respectively. The photo-response times of the device were shorter than those reported in previous studies. , However, compared with the n = 2 G–Au–P-PDs, the n = 1 G–Au–P-PDs had a lower dark current and faster photo-response time (Figure S13c,d). For the quasi-2D perovskite, the reduction of quantum well thickness, ion migration, and vacancy defect decrease can effectively confine the charge transport within the quantum plane, leading to a severe charge carrier recombination, resulting in both the dark current and photocurrent decrease. , Therefore, the quasi-2D P-PDs with small quantum well thickness showed great potential for ultra-fast photon detection.…”
Section: Resultsmentioning
confidence: 62%
“…As shown in Figure a, under light illumination, the perovskite absorbs photons and produces a large number of electron–hole pairs. The Au nanoarray contributes to photoinduced electron and hole generation, owing to the enhanced SLPR field. , Moreover, owing to the difference between the work function of the metal and perovskite for an electron transfer, a Schottky junction will be generated at the interface between the perovskite and Au nanoarrays, forming an interfacial electric field from the perovskite to the Au nanoarray layer. The electron barrier in the interface layer can reduce the charge recombination and loss and thus effectively promote the separation and transfer of electron hole pairs. , On the other hand, because the Fermi energy level between the graphene and perovskite is inconsistent, the separation and transfer of electron–hole pairs occurred.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the asymmetric plasmonic nanostructures can provide an extra polarization sensitivity to photodetectors based on low-dimensional materials, which further expand their applicability. , Moreover, PCs and DBRs are usually made of large-scale periodic nanostructures on rigid substrates, which is clearly not feasible for flexible devices, , while self-assembled plasmonic nanostructures can provide mechanical tension-offset and thus retain the original optical response under strain . Recently, a few studies have demonstrated plasmon-enhanced flexible, lead-based perovskite photodetectors yet with limited photocurrent enhancement, , which could be attributed to the fact that the perovskite films were directly deposited on the surface of noble metal nanostructures without introducing dielectric spacers between them. Although metallic nanostructures supporting localized surface plasmon resonance (LSPR) can significantly increase the light absorption of the active materials next to them, typically within a few tens of nanometers around them, energy transfer and charge transfer from the perovskite materials to the metal nanostructures could also occur and cause dramatic loss of photogenerated electron–hole pairs.…”
Section: Introductionmentioning
confidence: 99%